2019
DOI: 10.1097/md.0000000000014831
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic navigation bronchoscopic dye marking for localization of small subsolid nodules

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 28 publications
(44 reference statements)
0
10
0
Order By: Relevance
“…It is recommended for patients with emphysematous lung disease or COPD since it is associated with less complications such as pneumothorax and bronchial hemorrhage 16,17 . It also has the advantage of improved patient comfort as it is carried out under general anesthesia, and is a seamless procedure between localization and surgery without moving settings, therefore minimizing procedure time and risk 18,19 . The bronchoscopic approach facilitates entry into the regions that are not easily accessible by the percutaneous approach, such as nodules located near the costophrenic angle or under the scapula (such as the mediastinal side and the craniodorsal part obscured by the scapula) 7,8 .…”
Section: Discussionmentioning
confidence: 99%
“…It is recommended for patients with emphysematous lung disease or COPD since it is associated with less complications such as pneumothorax and bronchial hemorrhage 16,17 . It also has the advantage of improved patient comfort as it is carried out under general anesthesia, and is a seamless procedure between localization and surgery without moving settings, therefore minimizing procedure time and risk 18,19 . The bronchoscopic approach facilitates entry into the regions that are not easily accessible by the percutaneous approach, such as nodules located near the costophrenic angle or under the scapula (such as the mediastinal side and the craniodorsal part obscured by the scapula) 7,8 .…”
Section: Discussionmentioning
confidence: 99%
“…More recently, ENB‐guided dye marking has been proven as a valuable method in thoracic surgery. The success rate of ENB‐guided localization for small lung lesions ranges from 97.2% to 100% 8 . In this study, we aimed to explore the feasibility of the ENB‐guided dye marking method to identify the subsegmental bronchus in subsegmentectomy.…”
Section: Discussionmentioning
confidence: 99%
“…The success rate of ENB‐guided localization for small lung lesions ranges from 97.2% to 100%. 8 In this study, we aimed to explore the feasibility of the ENB‐guided dye marking method to identify the subsegmental bronchus in subsegmentectomy. Our research has confirmed that the ENB‐guided dye marking method is feasible and effective for identification of the subsegmental bronchus.…”
Section: Discussionmentioning
confidence: 99%
“…All marked nodules were completely resected thoracoscopically. Technically, we found a pathway with an obtuse approach angle should be selected to increase the navigation accuracy [33]. If the lesion is located in an area that requires an acute angle, the localization is not feasible, and we often have to use CT guided technique.…”
Section: The Third Dilemma: How To Localize Ggn?mentioning
confidence: 99%